Antiamoebic activity of plant‑based natural products and their conjugated silver nanoparticles against Acanthamoeba castellanii (ATCC 50492) - Anwar, Areeba (2020)
Acanthamoeba spp. are the causative agent of Acanthamoeba keratitis and granulomatous amoebic encephalitis (GAE). The current options to treat Acanthamoeba infections have limited success. Silver nanoparticles show antimicrobial effects and enhance the efficacy of their payload at the specific biological targets. Natural folk plants have been widely used for treating diseases as the phytochemicals from several plants have been shown to exhibit amoebicidal effects. Herein, we used natural products of plant or commercial sources including quercetin (QT), kolavenic acid (PGEA) isolated from plant extracts of Polyalthia longifolia var pendula and crude plant methanolic extract of Caesalpinia pulcherrima (CPFLM) as antiacanthamoebic agents. Furthermore, these plant-based materials were conjugated with silver nanoparticles (AgNPs) to determine the effects of the natural compounds and their nanoconjugates against a clinical isolate of A. castellanii from a keratitis patient (ATCC 50492) belonging to the T4 genotype. The compounds were conjugated with AgNPs and characterized by using ultraviolet visible spectrophotometry and atomic force microscopy. Quercetin coated silver nanoparticles (QT-AgNPs) showed characteristic surface plasmon resonance band at 443 nm and the average size distribution was found to be around 45 nm. The natural compounds alone and their nanoconjugates were tested for the viability of amoebae, encystation and excystation activity against A. castellanii. The natural compounds showed significant growth inhibition of A. castellanii while QT-AgNPs specifically exhibited enhanced antiamoebic effects as well as interrupted the encystation and excystation activity of the amoebae. Interestingly, these compounds and nanoconjugates did not exhibit in vitro cytotoxic effects against human cells. Plant-based compounds and extracts could be an interesting strategy in development of alternative therapeutics against Acanthamoeba infections.